2017
DOI: 10.1177/2045893217694175
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up tricuspid annular plane systolic excursion predicts survival in pulmonary arterial hypertension

Abstract: Few studies have examined the utility of serial echocardiography in the evaluation, management, and prognosis of patients with pulmonary arterial hypertension (PAH). Therefore, we sought to evaluate the prognostic significance of follow-up tricuspid annular plane systolic excursion (TAPSE) in PAH. We prospectively studied 70 consecutive patients with PAH who underwent baseline right heart catheterization (RHC) and transthoracic echocardiogram, who survived to follow-up echocardiogram after initiation of PAH th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 32 publications
(74 reference statements)
2
38
2
3
Order By: Relevance
“…The key strength of TAPSE is its simplicity as it can be measured on all ultrasound machines. It has been shown to have prognostic value in a variety of conditions which may affect the RV such as heart failure with preserved or reduced ejection fraction [20] and pulmonary hypertension [21]. As with all regional assessments of function, the obvious assumption made is that the longitudinal function of the RV free wall is indicative of function of the RV as a whole.…”
Section: [ 6 2 _ T D $ D I F F ] Global Assessment Of the Right Ventrmentioning
confidence: 99%
“…The key strength of TAPSE is its simplicity as it can be measured on all ultrasound machines. It has been shown to have prognostic value in a variety of conditions which may affect the RV such as heart failure with preserved or reduced ejection fraction [20] and pulmonary hypertension [21]. As with all regional assessments of function, the obvious assumption made is that the longitudinal function of the RV free wall is indicative of function of the RV as a whole.…”
Section: [ 6 2 _ T D $ D I F F ] Global Assessment Of the Right Ventrmentioning
confidence: 99%
“…Specifically, follow-up TAPSE ≥ 2 cm was associated with a decrease in all-cause mortality (hazard ratio = 0.21, 95% CI = 0.08, 0.60) and improved WHO functional class and 6-minute walk distance. 18 Prior to a study published by Sivak et al, it was unclear how much right atrial function contributed to RV function. Because total RV function is largely due to longitudinal shortening, Sivak et al hypothesized that the increased distance between RV base and apex that occurs during right atrial systole is an important contributor to overall RV function.…”
Section: Rv Function Tapsementioning
confidence: 99%
“…Further work will need to be done on how RV morphology changes over time, especially in patients with PH PVD , where reverse RV remodeling will transform RV morphology closer to normal. Prior work has shown that RV dimension, area, and the RV:LV ratio decline with PAH treatment . However, these studies did not focus specifically on changes in the sRV b/a over time.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has shown that RV dimension, area, and the RV:LV ratio decline with PAH treatment. 30,31 However, these studies did not focus specifically on changes in the sRV b/a over time. Future studies are also needed to evaluate the relationship between RV morphology and RV strain measures, as well as the reliability of sRV b/a to predict pulmonary vascular disease in patients with heart failure with poor LV function with LVEF < 50%.…”
Section: Discussionmentioning
confidence: 99%